2017
DOI: 10.1038/s41598-017-12708-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Glucose Powered Biofuel Cell Anode Developed by Polyaniline-Silver as Electron Transfer Enhancer and Ferritin as Biocompatible Redox Mediator

Abstract: Polyaniline-silver (PANI-Ag)/ferritin (Frt)/glucose oxidase (GOx) biocompatible anode was utilized for creating power from glucose. The synthesized nanocomposite was investigated by EIS (Electrochemical impedance spectroscopy), XRD (X-ray diffraction), FTIR (Fourier transform infrared spectroscopy), SEM (Scanning electron microscopy), CV (Cyclic voltammetry), and LSV (Linear sweep voltammetry) to know the morphology, crystallinity and electrochemical behaviour of the nanocomposite. The electroactive support (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…It has been observed that redox peak current is in directly proportional to the scan rate which suggests that the nitrate reduction by the GCE/PTH/MWCNT modified bioelectrode is dominated by a surface controlled phenomenon. Hence, it can be deduced from the results that scan rate has a significant effect on the electrochemical behavior of which includes a mixture of adsorption and diffusion controlled processes (Haque et al 2017(Haque et al , 2018Perveen et al 2017Perveen et al , 2018b. Water Supply Vol 00 No 0, 7…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…It has been observed that redox peak current is in directly proportional to the scan rate which suggests that the nitrate reduction by the GCE/PTH/MWCNT modified bioelectrode is dominated by a surface controlled phenomenon. Hence, it can be deduced from the results that scan rate has a significant effect on the electrochemical behavior of which includes a mixture of adsorption and diffusion controlled processes (Haque et al 2017(Haque et al , 2018Perveen et al 2017Perveen et al , 2018b. Water Supply Vol 00 No 0, 7…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…Moreover, they are also searching for an energy source to reduce environmental pollution and fossil fuel dependency. [ 1 ] Renewable energy sources like solar, wind, geothermal and biomass energy lack consistency in supply. Due to mobility issues, there is limited application of this energy in automobiles and remote areas.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of study is conducting on composite meterials for different applications because of high increase properties after making composite by involving individual initiators quality too [18][19][20][21][22][23][24][25][26][27][28]. Therefore, to improve the current response towards Cd 2+ concentration, especially in terms of response stability, we explored a conducting polymer-based composite-coated electrode material.…”
Section: Introductionmentioning
confidence: 99%